2022
DOI: 10.21608/ejp.2022.117996.1054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wheat Yellow Rust on Quantitative and Qualitative Grain Yield Losses under Egyptian Field Conditions.

Abstract: The purpose of the present study is to determine the effect of wheat yellow rust caused by Puccinia striiformis f. sp. tritici on quantitative and qualitative grain yield losses, in addition to predict them through regression model for each tested wheat variety, i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Nine resistant genotypes were grouped in one cluster, while the remaining eleven genotypes were gathered in another group. Additionally, Mabrouk et al (2022) tested yellow rust in different wheat genotypes. They employed the disease parameters i.e., FRS and AUDPC to differentiate the resistant and susceptible genotypes.Their results displayed substantial differences among the evaluated genotypes in FRS and AUDPC scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine resistant genotypes were grouped in one cluster, while the remaining eleven genotypes were gathered in another group. Additionally, Mabrouk et al (2022) tested yellow rust in different wheat genotypes. They employed the disease parameters i.e., FRS and AUDPC to differentiate the resistant and susceptible genotypes.Their results displayed substantial differences among the evaluated genotypes in FRS and AUDPC scores.…”
Section: Discussionmentioning
confidence: 99%
“…Nine resistant genotypes were grouped in one cluster, while the remaining eleven genotypes were gathered in another group. Additionally, Mabrouk et al. (2022) tested yellow rust in different wheat genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the mean values also revealed that stripe and leaf rust infection significantly affected yield and grain yield components' losses of all groups/categories/types of resistance in Indian wheat cultivars (Safavi 2015;Mabrouk et al 2022;Dinglasan et al 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Stripe rust, often known as yellow rust caused by Puccinia striiformis f. sp. tritici, is a devastating disease that affects wheat (Triticum aestivum L) in the major wheat-growing regions of the world [34,35]. The most cost-effective way to control the disease is to develop resistant wheat genotypes.…”
Section: Discussionmentioning
confidence: 99%